Endogenous Communication Among Lenders and Entrepreneurial Incentives - Padilla, A. Jorge; Pagano, Marco (Review of Financial Studies, 1997)
If banks have an informational monopoly about their clients, borrowers may curtail their effort level for fear of being exploited via high interest rates in the future. Banks can correct this incentive problem by committing to share private information with other lenders. The fiercer competition triggered by information sharing lowers future interest rates and future profits of banks. But, provided banks retain an initial informational advantage, their current profits are raised by the borrowers’ higher effort. This trade-off determines the banks’ willingness to share information. Their decision affects credit market competition, interest rates, volume of lending, and social welfare.